Faith’s Frontiers: An Exploration of Religious Syncretism and Cultural Adaptation in the “Guanyin/Madonna and Child” Painting - Zetong Liu; Hui Zeng; Junming Chen (Religions)
The Guanyin/Madonna and Child painting, housed in the British Museum, exemplifies a distinct amalgamation of Catholic and Buddhist elements. This academic study explores the religious syncretism within this artwork, set against the backdrop of Sino-Western cultural dynamics. By integrating socio-religious analysis with iconographic methods, this research highlighted the interplay between the two religious traditions and the broader trends of cultural adaptation and religious amalgamation. It was proposed that the painting, on display at the British Museum, reflects not only the European depiction of the Madonna of Humility but also the Jesuit missionary influence and the clandestine religious practices of Chinese Christians during periods of persecution. This investigation provided new perspectives on the nuances of religious syncretism and the evolution of religious imagery within the contexts of cultural exchanges and missionary initiatives, augmenting scholarly discussions on the dynamics between religious beliefs and societal frameworks.